Issues of different applicable substantive law rules to cross-border assignments of claim - Opengeima, Dina (Riga Graduate School of Law, 2019)
In recent years, there has been an increase of cross-border assignments of a claim due to various economic reasons. When an assignment of a claim is conducted cross-border, the parties involved in the process of the assignment are subject to different substantive law rules and formal requirements for the assignment of a claim. So far, there has not been any research conducted on the inconsistencies between the different substantive law rules and how these differences can lead to legal uncertainty. Thus, the main objective of the thesis was to find what are the inconsistencies of substantive law rules and formal requirements between different (EU and non-EU) countries.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law; Business law; Research Subject Categories::LAW/JURISPRUDENCE::Private law::Contract law